Determinants of Self-Care in Chronic Heart Failure: A Correlation Study of Social Support Dimensions - Tobi Pitora (Jurnal Keperawatan Profesional, 2026)
Chronic heart failure (CHF)  is rising at an alarming rate worldwide, along with other cardiovascular disorders. The long-term self-care of patients with CHF is necessary because the condition covers a variety of issues. Patients with CHF often benefit from social support as an external resource for symptom management. In multicultural countries such as Indonesia, decision-making is not solely individual but also involves the family. The purpose of this research is to find out how social support affects self-care practices among heart failure patients in Indonesia. This study employed a descriptive correlational approach and surveyed seventy-four participants. Sampling in this study employed a purposive sampling method, with respondents selected based on inclusion criteria. The sample size was determined using a rule of thumb. A self-care heart failure index (SCHFI) and the Medical Outcomes Study Social Support Survey (MOS-SS) were utilised in this research. To analyse the data, Pearson's statistical test was utilised. The results demonstrated that the average patient, who was 52 years old, experienced congestive heart failure (CHF). The study also found a significant relationship between social support and self-care in patients with congestive heart failure (0.239, p=0.040). This study also  shows that there is a weak correlation between social support and self-care. In summary: Another way social support might help people with CHF adhere to their treatment plan is by acting as a monitor. Confidence, maintenance, and management are all areas where social support can aid CHF patients.